History and Techniques for Conveying Saomai Dance in Lineage of Mrs. Buariao Rattanamaneeporn: ความเป็นมาและการถ่ายทอดฟ้อนสาวไหมสายสกุลช่างฟ้อนนางบัวเรียว รัตนมณีภรณ์ - Siriwattanakula, Bhudit; Saithongkum, Jintana (JOURNAL OF LANGUAGE, RELIGION AND CULTURE, 2022)
The objective of this article was to study the history and techniques for conveying Saomai dance by Mrs. Buariao Rattanamaneeporn. The study was qualitative research using relevant document studies and on-site data collection from interviews, observations, and dance practice. The data were then analyzed using descriptive research. The results showed that the history of Saomai dance in the lineage of Mrs. Buariao Rattanamaneeporn originated from family knowledge and patronage knowledge. There were five principles for conveying dance techniques: 1) relationship between instructor and recipient, 2) opportunity to pass on knowledge, 3) individual knowledge transfer, 4) group knowledge transfer, and 5) evaluation of knowledge transfer. The characteristics of inherited recipients could be divided into two types: single and individual. In this regard, the aim was to enable the recipient to perform the proper dance according to the set standards. Importantly, knowledge transfer in groups was assessed based on the limitations of the recipients in each group. Group recipients could be classified into three groups: concentration-restricted youth, physically-restricted seniors, and educational institutions with restrictions as defined in their curriculum.